2010
DOI: 10.1007/s00414-010-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

GSR deposition along the bullet path in contact shots to composite models

Abstract: In contact shots, all the materials emerging from the muzzle (combustion gases, soot, powder grains, and metals from the primer) will be driven into the depth of the entrance wound and the following sections of the bullet track. The so-called "pocket" ("powder cavity") under the skin containing soot and gunpowder particles is regarded as a significant indicator of a contact entrance wound since one would expect that the quantity of GSR deposited along the bullet's path rapidly declines towards the exit hole. N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 22 publications
0
8
1
Order By: Relevance
“…In a recent paper, Groβe Perdekamp et al [20] have demonstrated that in contact shots fired against composite pig skin-gelatine models, GSR particles were detectable also in the distal sections of the missile track up to the exit hole, while in our study no GSR particles were visible within and around the exit holes. These apparent divergences might have been caused by the different experimental models used (composite pig skin-gelatine model vs. human calf sections) and by the longer muzzle-to-target distances tested in our study (5,15, and 30 cm), which probably avoided the massive invasion of combustion products along the wound track.…”
Section: Discussioncontrasting
confidence: 52%
“…In a recent paper, Groβe Perdekamp et al [20] have demonstrated that in contact shots fired against composite pig skin-gelatine models, GSR particles were detectable also in the distal sections of the missile track up to the exit hole, while in our study no GSR particles were visible within and around the exit holes. These apparent divergences might have been caused by the different experimental models used (composite pig skin-gelatine model vs. human calf sections) and by the longer muzzle-to-target distances tested in our study (5,15, and 30 cm), which probably avoided the massive invasion of combustion products along the wound track.…”
Section: Discussioncontrasting
confidence: 52%
“…A comparison of contact shots and shots from an intermediate range clearly showed that gelatine disruption was significantly more extended in contact shots. The five experiments with muzzle contact showed GSR along the bullet path, particularly in the first and last parts, which corresponds to findings by Lieske et al [17] and is systematically documented by quantification of GSR by Große Perdekamp 6 Mean values of the WP for diverse distances et al [18]. A distance of 2 or 4 m and also 10 cm to the model already changed the character of the gelatine destruction.…”
Section: Discussionmentioning
confidence: 57%
“…The forensic investigation of incidents involving firearms routinely involves attempts to detect gunshot residue (GSR) on samples taken from different surfaces. The results of GSR analyses are often used in crime reconstruction to determine a variety of details including the shooting distance/trajectory, the characteristics of the firearm/ammunition combination and the nature of wounds (entry or exit) . Meanwhile, the detection of GSR on a sample taken from the hands, face or clothing of an individual may indicate that an individual has been in the vicinity of a discharging firearm or has made contact with surface onto which GSR has previously been deposited.…”
Section: Introductionmentioning
confidence: 99%